Strategies for Maintaining Customer Loyalty in the Face of Intense Competition Among Shipping Agencies at PT. Transuta Lintas Samudera, Banten Branch - Ismawati, Waode; Malau, April Gunawan; Sihombing, Derma Watty; Wiwoho, Boedojo; Kismantoro, Tri; Widjaja, Niken Sitalaksmi (Meteor STIP Marunda, 2023)
This study examines customer loyalty retention strategies at PT. Transuta Lintas Samudera's Banten Branch amid intensifying competition among 179 shipping agency companies operating in the Merak-Banten port area. Using a quantitative SWOT approach with data from 30 respondents and company operational records from August 2021 to July 2022, the study constructs weighted factor analysis matrices, a strategic position map, and a Quantitative Strategic Planning Matrix (QSPM) to identify and rank strategic alternatives. The internal analysis yields a weighted score of 2.87, while the external analysis produces 2.93, positioning the company in the Growth quadrant of the strategic position map. The QSPM ranking identifies intensifying promotional activities through online and offline channels as the highest-priority strategy (TAS = 6.35), followed by offering flexible pricing adjusted to customer workload capacity (TAS = 5.92). The study documents that the company met its monthly vessel target of 10 ships in only 1 of 24 months during the observation period, confirming that marketing restructuring is the most urgent intervention.